Praktik Reproduksi Sehat Remaja Putri Suku Anak Dalam (SAD) di Sepanjang Jalan Lintas Sumatera Provinsi Jambi - Asparian Asparian; Muhammad Rifqi Azhary; Sri Astuti Siregar; Usi Lanita (Prosiding Seminar Kesehatan Nasional, 2025)
The research "Mixed Method Research on Healthy Reproductive Practices of Young Women in Remote Indigenous Communities of the Anak Dalam Tribe along the Trans-Sumatra Road, Jambi Province" research with the type of Quantitative + Qualitative mixed methods research on the population of SAD young women along the Sumatra Cross Road, Jambi Province. The selection of research locations was carried out using multi-take sampling. Data collection, starting with stage I, collected quantitative data, selected using total sampling and analyzed using the SEM test with the Smart PLS application. Phase II collected qualitative data using an ethnographic approach through Focus Group Discussions with youth groups and stakeholders in 9 selected regions/villages. The research results show that there is a significant relationship between economic factors and individual factors, family and socio- cultural factors. Meanwhile, in the qualitative results, young women still do not have good knowledge about the reproductive health of young women.